Représenter le crime : permanences et inflexions (France, xixe siècle) - Dominique Kalifa (Cahiers Victoriens et Edouardiens)
Crime and delinquency have always been one of the major themes of popular culture and representations which fashion social imagination. In France, the July Monarchy (1830-1848) was a crucial moment in which representations, figures and renewed interpretations of this phenomenon converged. This trend has been very clearly described by Louis Chevalier in his book about working classes and dangerous classes (Classes laborieuses, et classes dangeureuses à Paris...). However, the last third of the nineteenth century was a new turning point : indeed following the rapid growth of cultural industries and the development of a parliamentary democracy, modes of representation began to change. The passion for inquiries which was then at its height, influenced the staging, the figures and the political assessment of criminal and delinquency cases, which are the origin of modern conceptions of insecurity.